2021
DOI: 10.1021/acsami.0c21995
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive, Rapid, and Automated Detection of DNA Methylation Based on Digital Microfluidics

Abstract: Biomarkers based on DNA methylation have attracted wide attention in biomedical research due to their potential clinical value. Therefore, a sensitive and accurate method for DNA methylation detection is highly desirable for the discovery and diagnostics of human diseases, especially cancers. Here, an integrated, low-cost, and portable point-of-care (POC) device is presented to analyze DNA methylation, which integrates the process of pyrosequencing in a digital microfluidic chip. Without additional equipment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…PMTs are able to convert photons into electrons followed by amplifying electrons multiple times, 94 Sensors & Diagnostics Critical review and thus amplify the signals and reduce the background noises for sensitive detection with a superior signal to noise ratio. 60,95 A straightforward way to use a PMT in the DMF platform is to manually place the light collection window (<1 cm) close above the surface of the device (∼5 mm of distance). Used in junction with magnetic bead-based immunoassays, this approach proved effective in quantifying human insulin and interleukin-6 (IL-6) in a glass substrate-based DMF platform (Fig.…”
Section: Compared With Conventional Z-dimension Cell Invasion Thismentioning
confidence: 99%
“…PMTs are able to convert photons into electrons followed by amplifying electrons multiple times, 94 Sensors & Diagnostics Critical review and thus amplify the signals and reduce the background noises for sensitive detection with a superior signal to noise ratio. 60,95 A straightforward way to use a PMT in the DMF platform is to manually place the light collection window (<1 cm) close above the surface of the device (∼5 mm of distance). Used in junction with magnetic bead-based immunoassays, this approach proved effective in quantifying human insulin and interleukin-6 (IL-6) in a glass substrate-based DMF platform (Fig.…”
Section: Compared With Conventional Z-dimension Cell Invasion Thismentioning
confidence: 99%
“…Through automation, the need for manual operation, technically trained operators, constant reagent supply and expensive equipment is heavily mitigated. Ruan et al demonstrated the effectiveness of automation through a fully automated electrode-controlled procedure to dispense uniform phosphate-buffered saline droplets for the detection of DNA methylation [ 48 ]. Thus, the variance that might have resulted from human error was effectively removed and the reliability and reproducibility of this assay were increased.…”
Section: Integrated Microfluidic-based Platforms (Imps)mentioning
confidence: 99%
“…As a burgeoning microfluidics technique, digital microfluidics (DMF) can manipulate discrete droplets of nanoliter to microliter volumes on an array of electrodes using the principle of electrowetting on dielectric (EWOD). [26][27][28] By programmed application of electrode potential, droplets can be individually dispensed, split, mixed and merged, allowing flexible reagent operations. Moreover, the DMF chip enables easily reconstructed surfaces, thus allowing for specific structure fabrication to trap single cells with an external device such as a magnetically controlled system for magnetic bead manipulation.…”
Section: Introductionmentioning
confidence: 99%